New Insights into Chronic Pancreatitis: Potential Mechanisms Related to Probiotics - Yingyu Pan; Jianing Li; Zhengyang Fan; Yonghao Chen; Xiaoxuan Huang; Dong Wu (Microorganisms)
Chronic pancreatitis is a progressive fibroinflammatory disorder with no currently satisfactory treatment. Emerging evidence suggests an association between gut microbial dysbiosis and chronic pancreatitis. Although direct causative evidence is lacking, it is hypothesized that the gut microbiota may play a pivotal role in modulating pancreatic function via the gut–pancreas axis. Thus, modulating the gut microbiota through the administration of probiotics or prebiotics may alleviate pancreatic disorders. In this review, we first propose the potential mechanisms by which specific probiotics or prebiotics may ameliorate chronic pancreatitis, including the alleviation of small intestinal bacterial overgrowth (SIBO), the facilitation of short-chain fatty acids’ (SCFAs) production, and the activation of glucagon-like peptide-1 receptors (GLP-1Rs) in the pancreas. Since there are currently no probiotics or prebiotics used for the treatment of chronic pancreatitis, we discuss research in other disease models that have used probiotics or prebiotics to modulate pancreatic endocrine and exocrine functions and prevent pancreatic fibrosis. This provides indirect evidence for their potential application in the treatment of chronic pancreatitis. We anticipate that this research will stimulate further investigation into the gut–pancreas axis and the potential therapeutic value of probiotics and prebiotics in chronic pancreatitis.